Tax Morale and Tax Compliance among SMEs: A Qualitative Study in Bukittinggi, Indonesia - Jennisa Dwina Indriani; Rusliza Binti Yahaya; Noor Lela Binti Ahmad (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
This study analyzes the influence of tax morale on tax compliance among micro, small, and medium-sized enterprises (MSMEs) in Bukittinggi. The low compliance indicates that regulatory approaches fail to foster voluntary compliance. This study employs a qualitative approach with a phenomenological design to understand the subjective experiences of MSME operators. Data were gathered through semi-structured interviews, observations, and documentation of 20 purposively selected MSME operators. The analysis used the Miles and Huberman interactive model. The study reveals that MSME operators experience tax compliance as a sharp psychological tension. Informants internalize tax morale through two distinct subjective structures: an internal obligation driven by social responsibility, and a sense of alienation caused by low government transparency. The phenomenological essence uncovers a phenomenon of administrative anxiety mixed with cultural resistance. Limited digital literacy and perceived procedural unfairness systematically erode the informants' intrinsic willingness to comply. This study establishes its novelty by capturing these deep emotional and socio cultural barriers such as the psychological weight of digital transition which traditional quantitative models overlook. This study contributes to tax behavior literature by integrating the psychological dimensions of small businesses. Practically, this study recommends transforming tax administration into an empathetic, community based framework, simplifying digital e-filing systems, and rebuilding institutional trust to foster sustainable compliance.